2015
DOI: 10.1002/pola.27906
|View full text |Cite
|
Sign up to set email alerts
|

Visible light‐induced thiol‐ene reaction: A new strategy to prepare Α,ω‐dithiol and Α,ω‐divinyl telechelic polythiolether oligomers

Abstract: A new strategy is developed to prepare both a,xdithiol and a,x-divinyl linear telechelic polythiolether oligomers by visible light induced thiol-ene chemistry in the presence of a fac-Ir(ppy) 3 photoredox catalyst. Polythiolether oligomers of well-defined end groups and controlled molecular weights have been successfully synthesized at varying monomer molar ratios of 1,4-benzenedimethanethiol (BDMT) to diethylene glycol divinyl ether (DEGVE).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…Compatibility with Thiol Click Chemistries : “Click” reactions are typically quantitative processes occurring under mild conditions and with a reactivity often orthogonal to those of most other functional groups; these versatile processes are extensively used in polysulfide synthesis. For example, thiol‐ene reactions are used in the preparation of (protected) initiators for episulfide polymerization, as the propagation (and cross‐linking) steps (see also the recent review by Araujo), as end‐capping reactions, for post‐polymerization curing, or as side‐chain modifiers . Michael‐type addition has also been widely used as a propagation reaction (for poly(ester sulfide)s), for end‐capping/chain extension, and cross‐linking purposes …”
Section: Oxidation (Ros)‐responsive Materialsmentioning
confidence: 99%
“…Compatibility with Thiol Click Chemistries : “Click” reactions are typically quantitative processes occurring under mild conditions and with a reactivity often orthogonal to those of most other functional groups; these versatile processes are extensively used in polysulfide synthesis. For example, thiol‐ene reactions are used in the preparation of (protected) initiators for episulfide polymerization, as the propagation (and cross‐linking) steps (see also the recent review by Araujo), as end‐capping reactions, for post‐polymerization curing, or as side‐chain modifiers . Michael‐type addition has also been widely used as a propagation reaction (for poly(ester sulfide)s), for end‐capping/chain extension, and cross‐linking purposes …”
Section: Oxidation (Ros)‐responsive Materialsmentioning
confidence: 99%
“…Recently, Tew and Sarapas reported the synthesis of functional poly(thioether)s, by radical step‐growth polymerizations between a functional dithiol and divinyl ether, and their application as lithium polymer electrolytes . In addition, various thiols and vinyl ethers have been subjected to radical step‐growth polymerizations for other applications . In contrast to the radical polymerizations for poly(thioether)s, the groups of Ruckenstein and Hashimoto independently reported the synthesis of poly(acetal)s by cationic step‐growth polymerization between a diol and divinyl ether in the presence of acidic catalysts such as PTSA, and then applied the acetal linkages as degradable units .…”
Section: Introductionmentioning
confidence: 99%
“…[43,44] In addition, various thiols and vinyl ethers have been subjected to radical step-growth polymerizations for other applications. [45][46][47][48] In contrast to the radical polymerizations for poly(thioether)s,t he groups of Ruckenstein and Hashimoto independently reported the synthesis of poly(acetal)s by cationic step-growth polymerization between ad iol and divinyl ether in the presence of acidic catalysts such as PTSA, and then applied the acetal linkages as degradable units. [49][50][51][52][53] However,t here have been neither reports on cationic stepgrowth polymerization between ad ithiol and divinyl ether nor on concurrent radical and cationic step-growth polymerizations,e xcept for ac ombination of radical thiol-ene stepgrowth radical polymerization and chain-growth cationic photopolymerization of vinyl ether for preparing crosslinked materials.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that both the M n and end‐group of the product can be controlled by adjusting the reaction time and the molar ratio of the monomers. [ 35 ] However, transition metal polypyridine complexes are very expensive and toxic.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction conditions between BDMT and DEGVE are mild and the reaction process is well‐controlled. [ 5,35 ]…”
Section: Introductionmentioning
confidence: 99%